Big data required updated system and software / Nurafiqah Mohd Rodzi, Saflina Azis and Mustafa Kamal Mat - Mohd Rodzi, Nurafiqah; Azis, Saflina; Mat, Mustafa Kamal (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Big data has completely transformed the accounting industry, bringing exciting opportunities and new challenges. As financial data grows rapidly in size, complexity, and speed, businesses are under increasing pressure to manage and analyze information more effectively. Staying competitive isn’t just about keeping up; it’s about making more intelligent, data-driven decisions. Outdated systems and manual processes can lead to inefficiencies, security risks, and compliance issues. To succeed, businesses must embrace modern technology, automate workflows, and invest in skilled professionals who can navigate the ever-evolving world of big data, ensuring accuracy, efficiency, and long-term business growth in the digital era.